2007
DOI: 10.1007/s00068-007-7068-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of Hypertonic Saline in the Treatment of Post-Traumatic Cerebral Edema: A Review

Abstract: Effective methods for treating cerebral edema have recently become a matter of both extensive research and significant debate within the neurosurgery and trauma surgery communities. The pathophysiologic progression and outcome of different forms of cerebral edema associated with traumatic brain injury have yet to be fully elucidated. There are heterogeneous factors influencing the onset and progress of post-traumatic cerebral edema, including the magnitude and type of head injury, age, co-morbid conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 133 publications
(190 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that, in experimental rat models of moderate TBI, serum magnesium level decreases and calcium/ magnesium level increases 22) . The use of hypertonic saline in the treatment of post-traumatic cerebral edema has been reported 8) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that, in experimental rat models of moderate TBI, serum magnesium level decreases and calcium/ magnesium level increases 22) . The use of hypertonic saline in the treatment of post-traumatic cerebral edema has been reported 8) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they also noted umbrella effect benefits including a reduced incidence of ARDS, pneumonia, sepsis and arrhythmias. The presumed benefits of HTS including preserved microvascular flow, decreased tissue oedema, and attenuated inflammatory response, may be particularly useful in brain-injured patients where cerebral oedema and intracranial hypertension lead to deleterious outcomes when aggressive fluid resuscitation is needed to maintain global haemodynamics [61]. More recently, several studies have compared HTS to mannitol for the control of intracranial hypertension, noting improved control with HTS [62].…”
Section: Hts In Traumatic Brain Injuries (Tbi)mentioning
confidence: 99%
“…In addition, studies [12], [13] demonstrated that HSS might have beneficial effects by modulating the excessive immune-inflammatory response on hemorrhagic shock. Particularly, HSS was said to play an important role in the treatment of traumatic brain injury via raising intracranial pressure and cerebral oxygenation [14], [15]. In recent study, authors [16] found that HSS also improved hemodynamic function by stimulating cardiac sympathetic nerve activity after hemorrhage shock.…”
Section: Introductionmentioning
confidence: 99%